CLASSIFICATION OF GUNSHOT FOREIGN BODIES MIGRATION - Lurin, I.A.; Khoroshun, E.M.; Makarov, V.V.; Nehoduiko, V.V.; Tertyshnyi, S.V.; Veryovkin, I.V.; Vastyanov, R.S. (World of Medicine and Biology, 2024)
The purpose of the study was to provide the classification features of the gunshot foreign bodies migration. We analyzed 90 cases of gunshot shrapnel blind wounds of different localization for a certain period, where there was a foreign body migration in different ways. The wounded which were admitted to the Military Medical Clinical Centre of the Northern Region of the Command of the Medical Forces of the Armed Forces of Ukraine, were examined by X-ray and, as indicated, using videoendoscopic methods. We distinguish the following classification features: the localization of the entrance hole; the place of migration initiation; the direction of migration; the number of foreign bodies; the structure of foreign bodies; the migration distance; the process of migration occurrence; the time of migration; the cause of migration; the frequency of migration; the foreign body fixation during migration; the volume of referral of migration surgical treatment. The identification of following three landmarks (the entrance hole, the place of migration starts and the place of detection), two stages (the wound channel and the migration corridor) and the direction of gunshot foreign bodies migration form a complete conception. The authors state that gunshot foreign bodies migration represents a separate type of a gunshot wound manifestation. The proposed original classification of gunshot foreign bodies migration allows to sort the data of clinical observations, which is of great importance for adequate and rapid diagnosis, determination of direct foreign body migration and its direction, and for effective treatment of gunshot wounds with phenomena of gunshot foreign body migration.
Keywords: gunshot wound; foreign bodies; migration; classification